2014
DOI: 10.1002/bio.2714
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive resonance Rayleigh scattering spectra method for the determination of quinolones in human urine and pharmaceutical preparation

Abstract: A new method based on resonance Rayleigh scattering (RRS) was proposed for the determination of quinolones (QNS) at the nanogram level. In pH 3.3-4.4 Britton-Robinson buffer medium, quinolones such as ciprofloxacin, pipemidic acid (PIP), lomefloxacin (LOM), norfloxacin (NOR) and sarafloxacin (SAR) were protonated and reacted with methyl orange (MO) to form an ion-pair complex, which then further formed a six-membered ring chelate with Pd(II). As a result, new RRS spectra appeared and the RRS intensities were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, the RRS spectra can be utilized to speculate molecular structure, charge distribution, and state of combination. Recently, the RRS technique has been widely applied to sensing metal ions, 8,9 biological molecules, [10][11][12] hazardous pollutants, 13,14 drug molecules, [15][16][17] dyes, [18][19][20] and so on. [21][22][23] The iron(III) cation is one of trace metal elements that play an important role in environmental and biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the RRS spectra can be utilized to speculate molecular structure, charge distribution, and state of combination. Recently, the RRS technique has been widely applied to sensing metal ions, 8,9 biological molecules, [10][11][12] hazardous pollutants, 13,14 drug molecules, [15][16][17] dyes, [18][19][20] and so on. [21][22][23] The iron(III) cation is one of trace metal elements that play an important role in environmental and biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the RRS method has been widely used for the determination of trace substances, for example, nucleic acids, [28] proteins, [29] inorganic ions, [30,31] organic compounds, [32,33] drugs, [34][35][36] etc. [37][38][39] Recent studies have shown that the RRS method can be also applied to the determination of antibiotics such as fluoroquinolones, [40,41] cephalosporins, [42] tetracyclines, [43] macrolides, [44] aminoglycosides, [45] etc. In the past few years, there have been reports on the quantitative analysis of NEO using the RRS method.…”
mentioning
confidence: 99%